The Effectiveness of Using the Cooperative Learning Model of FSLC Type on Students' Mathematical Reflective Thinking Ability - Bela Sutika; Rosmaiyadi Rosmaiyadi; Mariyam Mariyam; Sosuke Kotani (STKIP Singkawang, 2021)
The purpose of this study was to test the effectiveness of the cooperative learning model of Formulate Share Listen Create (FSLC) type on students' mathematical reflective thinking ability on the Pythagoras theorem. The research method used was quantitative. The population of the study was the VIII grade students of SMP Negeri 17 Singkawang, which amounted to 166 students. The sampling technique used was purposive sampling. The number of students who became the sample was 58 students. Data collection techniques in this study used measurement techniques through posttest questions, direct observation techniques through activity observation sheets, and questionnaire techniques through motivational questionnaires. The data analysis technique used was a one-sample t-test, Man-Whitney U-test, the percentage of activity, and the average analysis. The results showed that: (1) students completeness scores KKM ≥ 75 reached 75% with Zcount > Ztable = 0.12 > -1.96, (2) There was the difference of students' mathematical reflective thinking ability between using the cooperative learning model of FSLC type and the direct learning with an average score of 82.35 for the experimental class and 47.42 for the control class, (3) students’ activity was classified as active when the cooperative learning model of FSLC type was applied with a total percentage of 80.18% in the very high category, (4) students' learning motivation was high when the cooperative learning model of FSLC type was applied with an average of 4.15 in the high category. Thus, it could be concluded that the cooperative learning model of the FSLC type was effective for teaching students mathematical reflective thinking ability.